2018
DOI: 10.1177/2397198318774301
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Sonography findings of synovitis and tenosynovitis of hands and wrists in patients with systemic sclerosis

Abstract: Objectives: Validating musculoskeletal ultrasound features of the joints and tendons of the hands in a large scleroderma cohort. Methods: A total of 81 scleroderma patients participated in this prospective, cross-sectional study. Grayscale and power Doppler musculoskeletal ultrasound images of 13 joints and 5 tendons of the wrist and hand were obtained. Clinical assessment included modified Rodnan skin thickness score, joint count, and Scleroderma Health Assessment Questionnaire. Face validity, content validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The individual reductions in the TOF group varied within a larger range (− 0.12 mm to 0.57 mm) versus − 0.02 mm to − 0.17 mm in the MTX group. Musculoskeletal US may be used to assess articular and periarticular involvement in SSc patients [38][39][40][41]. Elhai et al showed that signs of tendon involvement were more frequent in SSc than in RA patients [42].…”
Section: Discussionmentioning
confidence: 99%
“…The individual reductions in the TOF group varied within a larger range (− 0.12 mm to 0.57 mm) versus − 0.02 mm to − 0.17 mm in the MTX group. Musculoskeletal US may be used to assess articular and periarticular involvement in SSc patients [38][39][40][41]. Elhai et al showed that signs of tendon involvement were more frequent in SSc than in RA patients [42].…”
Section: Discussionmentioning
confidence: 99%
“…The data from an interesting, prospective, cross-sectional study, using grayscale and Doppler musculoskeletal ultrasound, show that the Scleroderma Health Assessment Questionnaire–Disability Index correlated with musculoskeletal ultrasound erosions. The skin score correlated with tendinitis grayscale [ 50 ].…”
Section: Discussionmentioning
confidence: 99%